Asian firms' integrated reporting : a content analysis - Siyam, Yousuf (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2020)
Demand for holistic disclosure encompassing both financial and non-financial information has been overwhelming over the past few years. Accordingly, Integrated Reporting (IR) is a new way of corporate reporting to assist stakeholders in their decision making by providing useful and quality information as required by the International Integrated Reporting Framework (IIRF.) However, IR is a recent phenomenon and the quality of disclosures in integrated reports remains largely undiscovered. Herein, the first objective of the study is to assess the quality of 28 large Asian firms' integrated reports from 2014 to 2017. The second objective of the study is to examine trends of changes and improvements in the disclosure quality of large Asian firms' integrated reports over four years namely 2014, 2015, 2016 and 2017 in which the changes and improvements in the quality of reporting from one year to another year is explored and compared. Finally, the present study examines the gap between the current practices of IR and the requirements of IR. Content analysis using a checklist instrument was used to code and measure the quality of integrated reports and observe the quality trend over the years. In addition, the quality of integrated reports was analysed using the qualitative characteristics of accounting information prescribed by the Conceptual Framework to determine the quality and usefulness of disclosures in integrated reports. To examine the trend and changes over periods, a Mann Whitney U test was conducted to investigate the changes over period windows. The results generally indicate a low level of disclosure quality immediately following issuance of the IIRF. However, the quality gradually improved over later years, but the reports were still not in full compliance with the framework. The changes in the quality of reports between 2014 and 2015, and 2015 and 2016 were more significant, compared to the changes in quality between 2016 and 2017. Generally, amongst content elements of integrated reports, the quality of common disclosures in integrated reports is higher than innovative and distinctive disclosures required by the IIRF. Among the content elements, the items under “Organisational Overview and External Environment”, “Governance” and “Basis of Presentation” had the highest average of scores compared to the items “Future Outlook”, “Business Model” and “Risks and Opportunities.” Higher quality of information in integrated reports is associated with relevant, faithful and useful information presented. The findings of the study suggest that IR is increasing among Asian firms, however integrated reporting among Asian firms is less compared to western developed countries.